Pre-Colonial Warfare and Long-Run Development in India. Issue 643 (16th November 2021) - Dincecco, Mark; Fenske, James; Menon, Anil; Mukherjee, Shivaji
Abstract: Does pre-colonial history—and in particular the role of interstate warfare—help explain long-run development patterns across India? To address this question, we construct a new geocoded database of historical conflicts on the Indian subcontinent. We document a robust positive relationship between pre-colonial conflict exposure and local economic development today. Drawing on archival and secondary data, we show that districts that were more exposed to pre-colonial conflict experienced greater early state-making, followed by lower political violence and higher investments in physical and human capital in the long term.